274 Exome analysis to investigate autosomal dominant vasovagal syncope. Issue 10 (13th September 2018) - Jesuthasan, Aaron; Keogh, Michael; Chinnery, Patrick
Abstract : Introduction: Vasovagal syncope (VVS) is the most common cause of syncope in children and adults. Previous studies suggest a genetic component accounts for approximately 20% of cases, although the genes responsible are often unidentified. I studied the DNA of two distantly related individuals with VVS enrolled into the 100, 000 Genomes Project to identify causal mutations. Method: DNA was extracted from the patients, and analysed using an Ingenuity Variant Analysis program to detect the presence of mutations. The severity of each detected mutation was subsequently examined using two programs: Sorting Intolerant from Tolerant (SIFT) and Polymorphing Phenotyping v2 (PolyPhen-2). Results: Using Ingenuity Variant Analysis, a mutation in the ACE (Angiotensin Converting Enzyme), EPAS1 (Endothelial PAS Domain Protein 1 ) and PLCG2 (Phospholipase C Gamma 2) genes of the VVS patients were identified. Further analysis using SIFT and PolyPhen-2 indicated the ACE mutation was likely to produce a defective protein whilst the EPAS1 and PLCG2 mutations were unlikely to have any effect on protein function. Conclusion: My results support the involvement of the ACE mutation in the cause of VVS within the two studied patients. This may point towards a novel target for therapy within the individuals, should the findings be successfully validated.